Avaliação da erosividade das chuvas em diferentes locais do Estado de Minas Gerais - Pereira , Welington; da Silva, Telmo C A; Ribeiro Gomes, Fábio (Revista Ceres, 2025)
Using rainfall data from rain gauge records from 14 meteorological stations, a study was carried out of the erosivity of rainfall at selected localities in Minas Gerais State, Brazil. All 14 stations belong to the Fifth Meteorological District of the National Institute of Meteorology of the Ministry of Agriculture.